The experience of endoscopic resection of benign tumors of the esophagus - A. A. Smirnov (Вестник хирургии имени И.И. Грекова, 2018)
The objective of the study is to evaluate the safety and efficacy of the using of minimally invasive endoscopic methods in the treatment of submucosal esophageal tumors.Material and methods. The study included 89 patients with benign tumors of the esophagus. Endoscopic ultrasonography (EUS) was performed to determine the esophageal wall layer from which the tumor grows the size of the tumor and its relationship with the surrounding organs.Results. Submucosal tunneling resection was performed successfully in 73 patients. The average operation time was 84.5 minutes. In 16 patients, the tumor was removed by submucosal endoscopic dissection (SED). The average duration of ESD was 39.4 minutes. Among this group of patients we faced nonstandard cases of practical interest: leiomyomas of the upper part of the esophagus, plexiform leiomyomas and multiple leiomyomas. Each of the above types had its own specificity in diagnosis, treatment and postoperative management of patients.Conclusion. Submucosal esophageal tumors vary in types of growth, sizes, number of tumors, localization and its relationship with the surrounding organs. Scrupulous diagnosis of each case is necessary which will allow choosing the most appropriate treatment tactics for the patient.